Estimated breeding values of Frieswal bulls for the performance traits - GAUR, G K (The Indian Journal of Animal Sciences, 2014)
First lactation records of 791 daughters of 21 Frieswal bulls, maintained at different military farms during 1994 to 1999 were used to compute the breeding values. of young bulls for the performance trails and to eslimalethc relationships among them. Genetic and phenotypic trends in the performance traits were also estimated to assess the progress of the program. Estimated breeding values ranged from 852 to 1047 days for AFC; from 334 to 397 kg for WFC; from 121 to 173 days for FDP; from 146 to 204 days for FSP; from 404 to 504 days for FCI: from 2481 to 2768 kg for FLMY; from 9.0 to 16.4 kg for FPY and from 274 to 335 days for FLL Bulls's eslimated breeding values for peak yield had highest rank (0.74) and product moment (0.71) correlation with lactation yield. Top ranked bulls for FPY had accuracy of their EBV's only marginally lower (3.5104.9%) as compared to EBV's of FLMY It revealed that the Frieswal bulls could be selected on the basis of peak yield of their daughters to bring the reasonable genetic improvement in total lactation milk yieid. Genetic trends in most of the production trails were. positive and in reproduction trails were negative. This reveakd that there has been desirable improvement in the performance traits over lime. Annual genetic trends for FLMY and FPY were 15 and 0.06 kg and for FLL, AFC and FCI were 4.37, -4.82 and -11 12 days.